Design of multiband stack array antenna configuration for millimetre wave applications - Nibir, Abdur Rauful Jamil (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
The growing demand for wireless communication services stimulates the requirement of high speed of wireless system in future. To accomplish these demands, the use of millimeter wave bands appears inevitable due to the very large amount of spectrum that could be made available for that purpose. Hence to design antennas capable of working at a high frequency range is becoming a trend of current research. Many researchers are working on antenna for Mm-Wave wireless applications and the narrower bandwidth and lower gain are reported as main challenges in design. To design a multiband antenna in Mm-Wave is also a challenge. A novel antenna configuration is designed and modeled for multiband/wideband application. Dual-layer substrate technology is utilized in order to achieve multiple resonances at a higher bandwidth which is needed to cover the Mm-Wave electromagnetic spectrum ranges from 26 -40 GHz. Total of 25(5×5) antenna array configurations are simulated and analyzed to develop the model using Computer Simulation Technology (CST). Same number of resonances are achieved as number of radiating patches in lower layer. The operating frequencies of this design covers from single band 27.64 GHz, dual band 24.18, 28.77 GHz and triple band resonances 23.18, 25.63, 35.79 GHz, for quadruple band resonances 24.58, 26.77, 29.33, 34.43 GHz and quintuple band resonances 23.79, 25.37, 28.29, 31.69, 33.53 GHz. All ranges can be used for Mm-Wave applications. The maximum gain is achieved 14.02 dB from quintuple band antenna and the highest bandwidth is 2.29 GHz from the single band antenna. In the single and dual band antenna there is an impact of increasing the number of upper layer resonating patches as the return-loss gets better also the bandwidth gets wider but from the triple, quadruple and quintuple band there is almost little to no effect of the increasing number of patches in the upper layer. Three antennas out of those five optimized configurations are fabricated using Rogers RT5880 and tested using Vector Network Analyzer in order to validate the results. The test results are found 30.43 GHz at single band, 24.09, 29.23, 32.41 GHz for triple band, and 23.789, 25.37, 28.29, 31.69, 33.53 GHz for quintuple band. Although there is a slight frequency shift occurred in test results, still all the results show that single, triple and quintuple bands are achieved with -33.8 dB lowest return loss and 2.29 GHz highest bandwidth. The simulation results and the test results of the antenna are found in good agreement to each other.